Scalable Thermal Masking Technique for Postprocessing of Flexible Electronics. Issue 12 (12th August 2021) - Kashyap, Varun; Mosadegh, Bobak; Dunham, Simon
Abstract : Flexible electronics have found a wide variety of applications, especially in biomedical engineering, where their intrinsic safety and conformability provide for configurations of sensors and actuators that can accommodate complex anatomies and movement. Current scalable techniques in the manufacture of flexible electronics are limited by the challenges of working with novel, intrinsically stretchable materials, or using cost‐intensive clean room fabrication techniques needed to create strain accommodating geometries. Recently, a technique that allows for scalable postprocessing of flexible printed circuit boards (flex PCBs) to convert them to stretchable configurations is described. Herein, a mechanism for understanding this process based on a thermal masking phenomenon is described. Thermal simulation provides an understanding of the phenomenon and various aspects of the process. Copper traces are modeled along with Kapton insulating layer on ANSYS workbench and a Gaussian waveform is introduced to simulate a laser beam. An inhouse laser cutter is used to calibrate the simulations and an accurate predictive model is used to determine working conditions, resolution, and other parameters that affect the standardized usage of this process for various thicknesses of copper and Kapton that can be produced by most mass manufacturers. This process provides a path for cost‐effective manufacture of stretchable electronics. Abstract : A thermal masking technique for scalable processing of flex PCBs and cost‐effective manufacture of stretchable electronics is described. Thermal simulations are provided to support the understanding of this phenomenon and to highlight various aspects of the process. Limiting factors are discussed in terms of usability and ideal recommendations are mentioned to obtain best outcomes using this postprocessing technique.